Snow avalanches in western Canada: investigating change in occurrence rates and implications for risk assessment and mitigation. Issue 4 (2nd April 2016) - Sinickas, Alexandra; Jamieson, Bruce; Maes, Marc A.
Abstract : Snow avalanche frequency and magnitude, required for risk analysis, are best determined using historical occurrence records. In Canada, reliable records are sparse and relatively short term, extending back 30–50 years. Some Canadian avalanche forecasters suspect that climate change has increased avalanche activity in recent years. Should an increasing trend exist, analyses based on historical occurrence rates would underestimate future risk to people and infrastructure in mountain regions. We analyse 30 years of occurrence records to investigate whether a trend exists, and assess its strength. A Bayesian hierarchical model is used to estimate occurrence rate trends across six geographical zones in western Canada. The results suggest that natural avalanche occurrence rates have decreased or stayed constant; however, there is a very high level of uncertainty. This uncertainty will need to be factored into decision-making processes. To assist in this, we discuss the effect of long-term changes in avalanche occurrence rates in terms of consequences and vulnerability. We also recommend strategies for improving mitigation practices so that avalanche control operations can better adapt to changing and less predictable environments.